Early Printed Music and Material Culture in Central and Western Europe - Lindmayr-Brandl, Andrea; McDonald, Grantley (Music and Material Culture, 2021)
This book presents a varied and nuanced analysis of the dynamics of the printing, publication, and trade of music in the sixteenth and early seventeenth centuries across Western and Northern Europe. Chapters consider dimensions of music printing in Britain, the Holy Roman Empire, the Netherlands, France, Spain and Italy, showing how this area of inquiry can engage a wide range of cultural, historical and theoretical issues. From the economic consequences of the international book trade to the history of women music printers, the contributors explore the nuances of the interrelation between the materiality of print music and cultural, aesthetic, religious, legal, gender and economic history. Engaging with the theoretical turns in the humanities towards material culture, mobility studies and digital research, this book offers a wealth of new insights that will be relevant to researchers of early modern music and early print culture alike.